Creating a poutine food truck: Tabernasck - Levy, Arthur (2017)
This master project has the objective to develop a Business Plan which will enable the launch of a food truck that will serve poutine in the French Alps. The restaurant industry in the Savoie Mont Blanc area is highly responsible of the satisfaction people feel when going skiing. However, based on a ground study, we quickly realised that all restaurants look alike and propose the same local specialties. There clearly is a lack of restaurant diversity in the area. After analysing the current market with macro data and comparing them with field data I acquired with a questionnaire and a field trip, I decided to launch the first Poutine food truck in France. Poutine is the perfect meal while out skiing since it is quick and easy to eat while being warm and highly energetic. Associated with the mobility of a food truck, TABERSNACK will be able to travel all around the region and fulfil the need for variety felt by many skiers. We show in this business plan that food trucks are low capital requirement business that become quickly profitable. According to our forecasts, TABERSNACK should break even after 76 days of operation. It should reach a turnover of 86 811,21€ and a profit of 1 366,78€ the first year.